Parental representations after preterm birth: a narrative review - Hamon, Emeline; Bourdin, Béatrice; Le Driant, Barbara (Frontiers in Psychology, 2023)
Preterm birth affects nearly 15 million births annually worldwide and constitutes a considerable risk factor for atypical development. This birth context is a source of stress for the parents and often leads to an early separation between their child and them. Research on the influence of the birth status on the infant's attachment style has shown no systematic link between preterm birth and the development of insecure attachment in children born preterm.This has opened up research perspectives in understanding the role of environmental factors. A literature review was conducted to present an overview of the current findings on parental representations (PR), particularly maternal ones, and their role in the context of a preterm birth.PR quality appears to be associated with specific dyadic interaction patterns, thus exposing vulnerability factors. Studies exploring PR have pointed out the importance of considering parental mental elaboration mechanisms and contextual moderators in supporting socioemotional development among children born preterm. We discussed the challenges of investigating PR in the context of a preterm birth for future studies and emphasize the need for research studies to be conducted according to a developmental and non-deterministic perspective. This narrative review also aims to highlight the importance of family-centered care interventions in the context of a public policy focused on the child's "First 1,000 days" of life.